M19 The impact of co-morbidities on physical function and health status in chronic obstruction pulmonary disease (COPD). (14th November 2013) - Gale, NS; Albarrati, AM; Munnery, IC; Munnery, MM; Cockcroft, JC; Shale, DJ
Abstract : Background: Co-morbidities are of increasing importance in patients with COPD. However, the implications for function and health status have not been fully established. We hypothesised that the number of co-morbidities would relate to physical capacity, health status and impairments as measured by the comprehensive geriatric assessment (CGA) in COPD but not comparator subjects. Method: As part of the longitudinal Assessment of Risk in Chronic Airways Disease Evaluation (ARCADE), 500 patients with stable COPD (confirmed with spirometry) were compared to 141 comparator subjects (past or current smokers) free from respiratory disease. In all subjects previously diagnosed co-morbidities including; hypertension, hypercholesterolemia, angina, myocardial infarction, Stroke/TIA, atrial fibrillation, diabetes, and osteoporosis were recorded using a standardised health questionnaire. Spirometry, BMI, six minute walk distance (6MWD), the Timed Up and Go (TUG), and the number of impairments were determined using the CGA. Patients with COPD also completed the St George's Respiratory Questionnaire (SGRQ). Results: Patients and comparators were similar in age, gender and BMI, but differed in FEV1 % predicted 59 (20) and 105 (14) respectively (p < 0.01). Patients had more co-morbidities median (range) 2 (0–6) than comparators 1 (0–3) (p < 0.01). Of the patients, 24% had no co-morbidity, 54% had 1–2 co-morbidities and 22% had over 3 co-morbidities, while 54% of comparators had no co-morbidities and 45% had 1–2 co-morbidities (p < 0.01). Patients also had more impairments (CGA score), reduced 6MWD and increased TUG (all p < 0.001). The number of co-morbidities related to age, BMI, 6MWD, TUG, fibrinogen, the CGA and SGRQ and but not FEV1 in patients with COPD, and only to CGA score in comparators (Table 1 ). Conclusion: The number of comorbidities in COPD related to physical function, health status and impairments, independent of lung disease. Early management of co-morbidities may improve outcomes in patients with COPD.